Providing Acupressure Education and Training for Treating Headache to Society in Peken Hamlet, Renon Urban Village - Ida Ayu Anom Rastiti; Ida Ayu Suptika Strisanti; Ni Komang Sri Ariani (Jurnal Berkala Kesehatan, 2022)
One of the most frequent health issues that people deal with on a daily basis is headache. As they interfere with daily tasks and reduce productivity, headaches require significant treatment. Because of this, community service implementers are willing to provide counseling and acupressure training to the residents of Peken Hamlet, Renon Urban Village, in order to help them deal with their headaches. This service was performed on July 30, 2022, from 9:00 am to 12:00 pm WITA in the Peken Hamlet meeting room. Participants were initially split up into six small groups, each with five participants, and each group was supervised by a tutor. Before and after the activity, each group's members were requested to complete the pre-test form and post-test form. This community service was attended by 30 participants where the average age was 45.47 years with the majority of participants were female with percentage 19 people (63.3%) and the education background of the most of participants was university level (43.3%). The results of a Paired t-test showed that there had been a statistically significant improvement in the participants' understanding of acupressure with a p-value of 0.05. The average knowledge score on acupressure for headaches increased from pre-program (5.17±1.59) to post program (9.50±0.97). After the activity, participants' knowledge of acupressure for treating headaches is thought to have increased. The society will get a lot of benefits through this exercise. Those who frequently suffer from headaches can practice this simple acupressure technique at home because it has no adverse effects.